LISS 2013 Proceedings of 3rd International Conference on Logistics, Informatics and Service Science - Zhang, Runtong; Zhang, Zhenji; Liu, Kecheng; Zhang, Juliang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
Information and communication technology has helped to provide a more effective network infrastructure and development platform for logistics and service operations. In order to meet the needs of consumers, and particularly to promote low-carbon development processes, new types of services will also emerge. LISS 2013 is a prime international forum for both researchers and industry practitioners to exchange the latest fundamental advances in the state of the art and practice of logistics, informatics, service operations and service science. Experts and researchers from related fields will discuss current issues and future development opportunities, discuss and analyze developing trends and exchange the latest research and academic thought. The theme of the conference is Logistics and Service Science based on the Internet of Things.
Keynote Lectures -- Logistics Management -- Service Management -- Information Management -- Engineering Management -- Theory of Industrial Security and Development -- Tourism Management -- Advanced Research on Logistics/Supply Chain Management -- E-infrastructures and Technology -- Modeling and Its Application for Network Information Management -- Modeling Methods for Logistics Systems and Supply Chain.
Keywords: Economics; Industrial engineering; Engineering economy; Economics/Management Science; Production/Logistics/Supply Chain Management; Industrial and Production Engineering; Information Systems Applications (incl. Internet).; Engineering Economics, Organization, Logistics, Marketing